2021
DOI: 10.3390/jcm10061237
|View full text |Cite
|
Sign up to set email alerts
|

Medical Versus Surgical Treatment for the Management of Diabetic Foot Osteomyelitis: A Systematic Review

Abstract: A systematic review and quality assessment was performed to assess the management of diabetic foot osteomyelitis by medical or surgical treatment. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist was used. All selected studies were evaluated using the Cochrane Risk of Bias Tool to assess the risk of bias for randomized controlled trials. The literature was revised using PubMed (Medline) and Embase (Elsevier) up to September 2020 to identify clinical trials assessing med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 48 publications
(14 reference statements)
2
21
0
5
Order By: Relevance
“…Survey respondents identi ed a moderate need for further clinical trials testing key aspects of management. This is in keeping with the IWGDF guidelines and a recently published systematic review, which have highlighted uncertainties in many areas of managing DFI due to the lack of high-quality clinical trials (3,6). Surgeons that mainly worked in the private sector perceived greater value in RCTs testing wound dressings than those working at public hospitals.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Survey respondents identi ed a moderate need for further clinical trials testing key aspects of management. This is in keeping with the IWGDF guidelines and a recently published systematic review, which have highlighted uncertainties in many areas of managing DFI due to the lack of high-quality clinical trials (3,6). Surgeons that mainly worked in the private sector perceived greater value in RCTs testing wound dressings than those working at public hospitals.…”
Section: Discussionsupporting
confidence: 66%
“…The lack of high quality evidence means that there is limited consensus to guide optimal management of DFI, particularly in severe cases of DFI and diabetes-related foot osteomyelitis (6)(7)(8). This is echoed in a recent survey of Australian and New Zealand infectious diseases clinicians which reported limited consensus on how DFI was treated amongst this group of clinicians (9).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the selection of the best therapy to manage patients with DFO, we acknowledge that the typical profile of those patients who received medical therapy was different from those patients who received surgical treatment in our study. Unfortunately, and after decades, the selection of the best therapy for patients with DFO remains a matter of debate [ 32 ]. Nevertheless, there are published recommendations [ 12 , 15 ] that help clinicians select the best therapy according to the clinical presentation (e.g., soft-tissue infection or necrotising infection), vascular disease, or ulcer location and that determines if the surgery should be mandatory or not.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in such cases, bone resection and soft tissue debridement are almost mandatory to obtain a resolution of infection. Furthermore, a recently published systematic review [ 32 ] that compared medical versus surgical management of DFO concluded that efficient treatment of DFO requires selection of the appropriate method according to the indication and specific characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the detrimental effects of hyperglycemia, we should consider that both DFU risk factors and complications, such as infections or the structural alteration of the tissues, might persist after DFU remission 7 . Indeed, osteomyelitis represents a difficult challenge for clinicians, often requiring both medical and surgical approaches 8 . The choice of the procedures and their timing should be established on specific patients' characteristics, considering the most conservative and holistic approach to improve the prognosis 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%